2022
DOI: 10.1111/asap.12302
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of emergent psychological groupness predict stockpiling during the pandemic: Lack of trust, media exposure, and anxiety

Abstract: The stockpiling behaviors during the COVID‐19 pandemic emerged as an example for situations where cooperation is inhibited by lack of trust, media exposure, and increased anxiety. In this paper, I test the hypothesis that stockpiling results from social psychological factors that prevent psychological groupness and cooperation (e.g., low trust in governments and other citizens, high frequency of news exposure, high pandemic anxiety), rather than being an inherently selfish and uncontrollable panic behavior. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Lehberger et al (2021) similarly highlighted that subjective norms supporting stockpiling significantly promoted participants' intentions to stockpile nonperishable goods. Conversely, Uysal (2022) observed that social norms against stockpiling made individuals less prone to stockpiling. Hence, previous research suggests that customers who are influenced by subjective norms that support stockpiling are more likely to form stockpiling intentions.…”
Section: Literature Review Theoretical and Conceptual Framework And H...mentioning
confidence: 99%
“…Lehberger et al (2021) similarly highlighted that subjective norms supporting stockpiling significantly promoted participants' intentions to stockpile nonperishable goods. Conversely, Uysal (2022) observed that social norms against stockpiling made individuals less prone to stockpiling. Hence, previous research suggests that customers who are influenced by subjective norms that support stockpiling are more likely to form stockpiling intentions.…”
Section: Literature Review Theoretical and Conceptual Framework And H...mentioning
confidence: 99%